2004
DOI: 10.1007/s00284-003-4108-3
|View full text |Cite
|
Sign up to set email alerts
|

Oral Streptococci Exhibit Diverse Susceptibility to Human �-Defensin-2: Antimicrobial Effects of hBD-2 on Oral Streptococci

Abstract: We examined the antimicrobial effects of human beta-defensin-2 (hBD-2) on 17 species of oral streptococci to investigate the involvement of antimicrobial peptide activity in oral microflora development and the clinical use of the antimicrobial peptide for oral microflora control. Oral streptococci exhibit diverse levels of susceptibility to human beta-defensin-2 (hBD-2). Two major cariogenic bacterial species, Streptococcus mutans ( S. mutans) and S. sobrinus, were found to be susceptible to the peptide, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 12 publications
1
49
0
3
Order By: Relevance
“…In this age of antibiotic resistance, the idea of using natural antimicrobial peptides or their synthetic derivatives to combat bacterial and fungal infections is particularly appealing. The use of antimicrobial peptides as dental therapeutics to combat periodontal disease and caries has been posited, and a number of oral microbes have demonstrated sensitivity to these peptides in vitro (34,41,43,44,47,48). However, we have demonstrated that T. denticola and several other oral treponemes are not vulnerable to human ␤-defensins (9,10).…”
Section: Discussionmentioning
confidence: 75%
“…In this age of antibiotic resistance, the idea of using natural antimicrobial peptides or their synthetic derivatives to combat bacterial and fungal infections is particularly appealing. The use of antimicrobial peptides as dental therapeutics to combat periodontal disease and caries has been posited, and a number of oral microbes have demonstrated sensitivity to these peptides in vitro (34,41,43,44,47,48). However, we have demonstrated that T. denticola and several other oral treponemes are not vulnerable to human ␤-defensins (9,10).…”
Section: Discussionmentioning
confidence: 75%
“…The defensins and cathelicidins have broad antimicrobial activity against gram-negative and gram-positive bacteria and Candida albicans and are effective in vitro against oral microorganisms such as Streptococcus mutans, Porphyromonas gingi-valis, and Actinobacillus actinomycetemcomitans (5,13,25,35). The cathelicidins and ␣-and ␤-defensins act synergistically with other antimicrobials (19,24).…”
mentioning
confidence: 99%
“…It is interesting that the recombinant lysine variant of LTF expressed in an insect vector also induced an upregulation of epithelial production of human beta defensin 2 (hBD-2) (11). hBD-2 has been shown to have significant antibacterial activity against S. mutans and S. sobrinus, two cariogenic microbes (29). Conversely, hBD-2 has been shown to have little to no effect on several Gramnegative periodontal pathogens (30).…”
Section: Discussionmentioning
confidence: 99%